Optimizing the Implementation of Complete Systematic Land Registration (PTSL) at the Land Office as an Effort to Accelerate Land Registration - Purwantoko, Gilang Riyan; Darmadi, Nanang Sri; Riyanto, Taufan Fajar (TABELLIUS: Journal of Law, 2026)
This study aims to analyze: 1 Efforts to optimize the implementation of PTSL as a step to accelerate land registration in Grobogan Regency. 2) Obstacles and solutions in the implementation of PTSL in Grobogan Regency. This type of research is empirical legal research. The approach method in this research is a qualitative approach. The types of data in this research are primary and secondary data. The data collection method uses observation, interviews and library techniques (document study). The analysis in this research is descriptive. The results of the study concluded: 1) Efforts to optimize the implementation of PTSL as a step to accelerate land registration in Grobogan Regency have shown effective and targeted performance, despite being implemented in diverse social, geographical, and administrative conditions. This optimization is reflected in strengthening the regulatory basis, increasing human resource capacity, intensifying outreach to the community, adjusting technical methods of measurement and mapping, validating and digitizing land administration data, and strengthening coordination between stakeholders. The gradual implementation of PTSL, both during the high target of Fiscal Year 2024 and the limited target of Fiscal Year 2025, is still able to produce tangible outputs in the form of issuance and delivery of land title certificates and increasing public participation and legal awareness. 2) Obstacles in the implementation of PTSL in Grobogan Regency are still influenced by low public understanding and participation, limited human resources at the Land Office, difficult geographical conditions and field terrain, distance and accessibility of villages far from the center of government, disorderly village land administration especially related to Letter C, potential land boundary disputes, and limited financing capacity of underprivileged communities. To overcome these obstacles, operational and contextual solutions are needed, including increasing socialization and counseling of village-based land law, optimizing the work of officers and involving third parties in a controlled manner, adjusting measurement techniques according to geographical conditions, implementing outreach services, strengthening the role of village governments in land administration arrangements and verifying legal data, facilitating land boundary deliberations, and transparency and supervision of PTSL financing, so that the implementation of PTSL is not only oriented towards achieving targets, but also able to improve the quality of land registration and legal certainty of land rights for the community in a sustainable manner.